Orthotopic Neo-Bladder Repair Indications and Functional Results after Radical Bladder Cancer Cystectomies - Haris Hamid, Ghufran Ullah, Obaid Ur Rehman, Muhammad Yahya Hasan, Ali Dawood, Hassan Raza Asghar (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Our objectives were to list the surgical problems, assess the functional results, and communicate our indications for ONB reconstruction. Study Design: Retrospective/cross sectional study Methods: There were 35 instances in all that had ONB reconstruction following RC for bladder cancer. Sociodemographic information, clinical and pathological information, surgical indications, voiding, and metabolic outcomes at six and twelve months after surgery were among the data gathered. Using IBM-SPSS version 24.0, data analysis was carried out. Results: The included cases had mean age 58.38±12.76 years. There were 22 (62.9%) males and 13 (37.1%) females among all cases. Twenty-six (74.3%) and twenty-four (68.6%) of the children had acceptable nocturnal and diurnal continence at 12 months. In 28 patients (80%), the peak urine flow rates were acceptable, and in 29 patients (82.9%), the post-void residual volumes were acceptable. At 12 months after the inception of the ONB, 30 persons (85.7%) had normal sodium levels, 32 had normal potassium levels, and 33 had normal chloride levels. Conclusion: Our results provide valuable information about the functional outcomes linked to ONB reconstruction, showing that it produces acceptable incontinence and low rates of electrolyte imbalance. Keywords: ONB, RC, Bladder Cancer